MODEL INOVASI SISTEM PEMASARAN PERBANKAN SYARIAH BERBASIS FLOATING MARKET UNTUK PENCIPTAAN DAYA SAING (MODEL OF ISLAMIC BANKING MARKETING INNOVATION SYSTEMS BASED ON FLOATING MARKET FOR CREATION COMPETITIVENESS) - Diana Sulianti K. Tobing; Moehammad Fathorazzi; Gusti Ayu Wulandari (University of Merdeka Malang, 2016)
AbstractGovernment in implementing policies dual banking system in fact is still unrealized, whereas considerablemarket potential with many established Islamic banks. One solution offered is a marketing system innovationin Islamic banking market floating base. The purpose of this study identifies spiritual and floating marketbehavior and determine the factors that influence the customers decision in choosing Islamic banks based onpersonal and social nature. The study population is Islamic bank customers located in the region of Jember,Bondowoso, Situbondo, and Banyuwangi with a sample of 200 people. The research method used logisticregression analysis. The results achieved are the majority of customers are female, in the productive age, andemployees. The majority of customers are in a group associated with Islamic banks and conventional.